2017
DOI: 10.1111/ijfs.13536
|View full text |Cite
|
Sign up to set email alerts
|

Stability of antioxidant peptides from duck meat after post‐mortem ageing

Abstract: The stability of antioxidant peptides from aged duck meat during processing and simulated gastrointestinal digestion was investigated. The antioxidant peptides preserved a high stability in the presence of diverse NaCl or upon various time heating. The antioxidant activities were strengthened by the addition of 4-8% glucose or by heating at 100°C, whereas they were lost under alkaline conditions. During in vitro digestion, the antioxidant activities increased with pepsin treatment but then decreased following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
(56 reference statements)
1
5
0
Order By: Relevance
“…With the increase in the degree of hydrolysis, polar or charged moieties were exposed heavily and the peptides could become effective hydrogen or electron donors to reduce Fe 3+ -TPTZ complex. [35,36] This result is in accordance with that of You et al [20] , who found that the reducing power of loach protein hydrolysates significantly increased after simulated gastrointestinal digestion.…”
Section: Frap Of Simulated Gastrointestinal Digestionsupporting
confidence: 91%
See 1 more Smart Citation
“…With the increase in the degree of hydrolysis, polar or charged moieties were exposed heavily and the peptides could become effective hydrogen or electron donors to reduce Fe 3+ -TPTZ complex. [35,36] This result is in accordance with that of You et al [20] , who found that the reducing power of loach protein hydrolysates significantly increased after simulated gastrointestinal digestion.…”
Section: Frap Of Simulated Gastrointestinal Digestionsupporting
confidence: 91%
“…During the pepsin digestion, more hydrophobic amino residue side chain groups were expected to be exposed because the peptides were completely hydrolyzed, which would make the peptides more accessible to the DPPH radicals and stabilized toward the DPPH radicals. [35,36] However, further digestion with trypsin resulted in a sharp decrease in DPPH radical scavenging activity. That is because, during the trypsin digestion, the peptides were intensively hydrolyzed, which could lead to high accumulation of shorter peptides and free amino acids, thus making the digestion sample to be more hydrophilic.…”
Section: Dpph Radical Scavenging Of Simulated Gastrointestinal Digestionmentioning
confidence: 99%
“…Generally, bioactivities of peptides are closely related to amino acid composition, sequences, hydrophobicity, etc. In this work, we mainly focused on the bioactivity changes of crude peptides and the effect of cooking and in vitro simulated gastrointestinal digestion on these parameters, thus mainly using amino acid analysis and hydrophobicity analysis methods as indicated in other reported works in the literature [ 4 , 10 , 37 ]. Bioactive peptides are usually characterized by short sequences of approximately 2 to 30 amino acids in length and a low molecular weight [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, considering the complexity and versatility of natural antioxidants in vivo and in vitro , especially for Xuanwei ham with complicated ingredients, it is more scientific and systematic to comprehensively evaluate antioxidant activity by multiple methods. Generally, most meat-derived antioxidant peptides have demonstrated their properties by a range of in vitro assays, which have been widely accepted and reported by an increasing number of studies [ 37 , 39 , 45 ]. On the basis of the chemical reactions involved, major antioxidant capacity assays were divided into electron transfer (ET) reaction-based methods and hydrogen atom transfer (HAT) reaction [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The significant decline of activity under alkaline condition could be explained by the following several aspects. One reason is the formation of peptide isomers in the racemization reaction occurred under alkaline condition, and it is known that differences in bioactivities existed between isomers (Liu et al, 2017a). In addition, the higher pH will promote the possibility of deamination and lead to changes in structure and conformation of peptide and thereby the change of activity.…”
Section: Phmentioning
confidence: 99%